Perhitungan Harga Pokok Produksi Dalam Menentukan Tarif Biaya Overhead Pabrik (Studi PT. Sigi Multi Sejahtera Pasuruan Tahun 2018) - Nurul Safariah; Dian Hakip Nurdiansyah (Peneliti.net, 2022)
This research was conducted on the basis of the number of companies that have not used standard factory overhead rates in calculating the cost of production. The use of standard factory overhead rates allows for a consistent and reasonable allocation to each unit of output for the entire production period. The standard rate of factory overhead costs needs to be determined to avoid unequal assignment to each unit of output throughout the production period. Factory overhead costs of PT. Sigi Multi Sejahtera which is included in the calculation of the cost of production is calculated based on the actual costs incurred at the end of the production period. PT. Sigi Multi Sejahtera has not determined the rates for each of the factory overhead costs. After the standard factory overhead rates are determined, there is a significant difference between the actual factory overhead costs incurred and the factory overhead costs charged because the actual production amount exceeds the planned production amount. The difference is treated as an adjustment to the Cost of Goods Sold and ending inventory accounts.